National And Cultural Characteristics of Modal Category (Analysis Of French and Uzbek Fairy Tales) - Juraeva Malokhat Mukhammadovna (Genius Publishing Group, 2021)
This article deals with the concept of "fairy tale", one of the oldest and most popular genres of folklore, the "modality category", which has a universal character in linguistics, is an important functional aspect of communication, and is of great importance for understanding the essence of language. The two incompatible language sections analyze the national and cultural features of French and Uzbek fairy tales.
Keywords: Concept; lingvokulturema; rationalism; cultural units